2013
DOI: 10.1371/journal.pone.0056015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IgE-Receptors in IgE-Dependent Airway Smooth Muscle Cell Remodelling

Abstract: BackgroundIn allergic asthma, IgE increases airway remodelling but the mechanism is incompletely understood. Airway remodelling consists of two independent events increased cell numbers and enhanced extracellular matrix deposition, and the mechanism by which IgE up-regulates cell proliferation and extracellular matrix deposition by human airway smooth muscle cells in asthma is unclear.ObjectiveCharacterise the role of the two IgE receptors and associated signalling cascades in airway smooth muscle cell remodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 45 publications
4
60
0
4
Order By: Relevance
“…One earlier study showed that the median time to recovery was 6 d (1-14) for peak expiratory flow rate (PEFR) and 7d (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) for symptoms, but recovery of PEFR to baseline values was complete in only 75.2% of exacerbations at 35d [34]. In our study, 18% (51/273) of the COPD patients were enrolled within 2~4 weeks after an exacerbation, when the lung functions were still recovering at least in some of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One earlier study showed that the median time to recovery was 6 d (1-14) for peak expiratory flow rate (PEFR) and 7d (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) for symptoms, but recovery of PEFR to baseline values was complete in only 75.2% of exacerbations at 35d [34]. In our study, 18% (51/273) of the COPD patients were enrolled within 2~4 weeks after an exacerbation, when the lung functions were still recovering at least in some of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the serum total IgE (T-IgE) may be a more sensitive marker for hypersensitive condition of the host. Meanwhile, it is possible that serum IgE, which was shown to be related to airway inflammation and remodeling in asthma [6][7][8][9], may have effects on symptoms and lung function of COPD. Until now, data on the allergic status of COPD patients and its association with clinical symptoms and lung function are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Roth et al [32] observed that IgE increases airway remodelling in asthma by activation of proliferation of smooth muscle cells as well as by increased extracellular deposition of pro-inflammatory collagen (Types: I, III, VII) and fibronectin. Such findings imply a potential role of omalizumab in airway remodelling.…”
Section: Pharmacodynamic Properties Of Omalizumabmentioning
confidence: 99%
“…Furthermore, it has been recently reported that omalizumab can significantly decrease the concentration of endothelin-1 (ET-1) -a peptide involved in the pathogenesis of airway structural changes such as subepithelial fibrosis and proliferation of bronchial smooth muscle cells -in the exhaled © C I C E d i z i o n i I n t e r n a z i o n a l i breath condensate of patients with severe persistent allergic asthma (44). On the other hand, pre-treatment with omalizumab of airway smooth muscle cells obtained from allergic asthmatic patients significantly decreased IgE-dependent production of extracellular matrix proteins such as collagen type I, collagen type III and fibronectin (45). Recent preliminary findings, obtained in a limited number of asthmatic patients by means of computed tomography (CT) imaging, have shown that omalizumab reduced airway wall thickness and increased the bronchial luminal area (46).…”
Section: Preclinical and Clinical Studiesmentioning
confidence: 99%